Pengaruh Kompetensi, Motivasi, Sarana Prasarana, dan Iklim Sekolah terhadap Kepemimpinan Kepala Sekolah di Sekolah Dasar Negeri - Jamaluddin Malik; Sutaryat Trisnamansyah; Agus Mulyanto (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2021)
The main purpose of this study was to analyze the contribution of competence, motivation, infrastructure, and school climate to the leadership of the principal. The research method used in this study is quantitative with questionnaire data collection techniques given to 202 public elementary school principals in South Lampung Regency as research samples. The results of data collection were then analyzed using path analysis and multiple regression techniques. The findings of this study are (1) competence contributes significantly to the principal's leadership by 77.4% which is categorized as strong/high influence (2) motivation contributes significantly to the principal's leadership by 61.1% which is categorized as moderate/sufficient influence (3) means infrastructure contributed significantly to the principal's leadership by 97.8% which was categorized as very strong/very high (4) school climate contributed significantly to the principal's leadership by 85.7% which was categorized as strong/high (5) competence, motivation, facilities infrastructure, and school climate simultaneously contributed significantly to the leadership of the principal by 98.1% which was categorized as very strong/very high influence.